The informatively-factor analysis as new information technology - Али, Аль-Аммори (Proceedings of National Aviation University, 2010)
The informatively-factor analysis of processes of flight as new perspective approach is offered taking into account polifactorial. Historical bases of origin are examined; development of factor analysis and information theory, the value of informatively-factor analysis is underlined for providing of safety and efficiency of flight.